Characterization of vacuolar amino acid transporter from Fusarium oxysporum in Saccharomyces cerevisiae. Issue 12 (2nd December 2015) - Lunprom, Siriporn; Pongcharoen, Pongsanat; Sekito, Takayuki; Kawano-Kawada, Miyuki; Kakinuma, Yoshimi; Akiyama, Koichi
Abstract: Fusarium oxysporum causes wilt disease in many plant families, and many genes are involved in its development or growth in host plants. A recent study revealed that vacuolar amino acid transporters play an important role in spore formation in Schizosaccharomyces pombe and Saccharomyces cerevisiae . To investigate the role of vacuolar amino acid transporters of this phytopathogenic fungus, the FOXG_11334 ( FoAVT3 ) gene from F. oxysporum was isolated and its function was characterized. Transcription of FoAVT3 was upregulated after rapamycin treatment. A green fluorescent protein fusion of FoAvt3p was localized to vacuolar membranes in both S. cerevisiae and F. oxysporum . Analysis of the amino acid content of the vacuolar fraction and amino acid transport activities using vacuolar membrane vesicles from S. cerevisiae cells heterologously expressing FoAVT3 revealed that FoAvt3p functions as a vacuolar amino acid transporter, exporting neutral amino acids. We conclude that the FoAVT3 gene encodes a vacuolar neutral amino acid transporter. Abstract: : Localization of vacuolar neutral amino acid transporter, GFP-FoAvt3p, in Fusarium oxysporum . FoAvt3p (green) functions as transporter of neutral amino acids from vacuole (blue) to cytosol.